Tongging Hotel Resort With Neo Vernacular Approach - Firman Eddy; Dariyan Arya Wijaya (International Journal of Architecture and Urbanism, 2020)
Indonesian’s nature has a combination of a tropical climate and is the largest and most island nation in the world. Indonesia also has many natural tourism sites that are already well-known abroad. One of them is Lake Toba. Lake Toba is the largest and deepest lake in Southeast Asia. These tourist attractions are also supported by a cultural heritage that is rich with many tribes and customs that spread throughout Indonesia. Resort hotels are one of the supporting facilities in the tourist area. The design of the Tongging resort hotel raises the theme of neo vernacular. The problem posed was "How to design Resort Hotels using the neo-vernacular architectural approach?". Using the neo-vernacular school aims to arouse the culture and customs of the environment. Because we know the Tongging area is a Batak tribe area, which is a very thick tribe with traditions and customs. The resort hotel design Tongging is designed using ornamentation and formations, which are more directed to the Siwaluh Jabu traditional house by using qualitative methods because it is rational and planned precisely with the location of the site. Tongging resort hotel can be a resort hotel that does not leave the local culture and can become an icon in the hope that it can still preserve the existing customs or culture.